2009
DOI: 10.1111/j.1365-3083.2009.02289.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Administration of Ethanol in Mice Deviates Antigen Presentation Activity Towards B Cells

Abstract: Alcohol has a variety of short‐ and long‐term effects on cell‐mediated and humoral immune response. Herein, we have characterized the impact of high‐dose EtOH administration on phenotypic and functional features of murine APC subsets, including dendritic cell (DC), macrophages and B cells. Impaired cytokine synthesis and Leishmania‐phagocytosis was observed in peritoneal macrophages following EtOH administration. Moreover, EtOH exposure led to decreased levels of splenic myeloid DC and increased percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Previous studies from our group have demonstrated that short-term acute administration of EtOH might disturb the ability of developing OVA-oral tolerance by deviate the antigen presentation activity toward B cells (Andrade et al, 2009). Moreover, we have shown previously that this deviation in antigen presentation toward B cells led to an increased activation status of CD4 + T cells and this increase is associated with particular immune responses as detected by elevated IL-4 production and augmented levels of serum IgE.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies from our group have demonstrated that short-term acute administration of EtOH might disturb the ability of developing OVA-oral tolerance by deviate the antigen presentation activity toward B cells (Andrade et al, 2009). Moreover, we have shown previously that this deviation in antigen presentation toward B cells led to an increased activation status of CD4 + T cells and this increase is associated with particular immune responses as detected by elevated IL-4 production and augmented levels of serum IgE.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it has been suggested that the gastric compartment is also involved in this phenomenon, as allergic-type gastritis induced by acute short-term administration of EtOH impairs the establishment of oral tolerance mechanisms (Andrade et al, 2006). In fact, increasing evidences suggest that alcohol abuse lead to imbalanced immunomodulatory events, mainly impacting antigen presentation (Andrade et al, 2009;Heinz and Waltenbaugh, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…TLR pathways are involved in the maturation and immunoglobulins synthesis of B cells. However, another study showed that short-term ethanol treatment at high dose down-regulated splenic macrophages and DCs activity via enhancing B cells function as the antigen-presenting cell, and eventually facilitating a microenvironment that leads to increased activation of CD4 + T cells (121). The roles of B cells within the spectrum of ALD deserve to be further elucidated with mechanistic studies required.…”
Section: Adaptive Immune Cellsmentioning
confidence: 99%